Racial/Ethnic Differences in Trust in Health Care: HIV Conspiracy Beliefs and Vaccine Research Participation - Westergaard, Ryan P. (Springer US, 2013)
BACKGROUND: Prior research has documented a high prevalence of conspiracy beliefs about the origin of the human immunodeficiency virus (HIV) and the role of the government in the acquired immunodeficiency syndrome (AIDS) epidemic, particularly among racial and ethnic minorities in the United States. Whether such beliefs are a barrier to participation in HIV prevention research is not known. OBJECTIVE: To understand the prevalence of HIV conspiracy beliefs and their relationship to willingness to participate in HIV vaccine research among three racial/ethnic groups. DESIGN: Cross-sectional survey. PARTICIPANTS: Six hundred and one community-recruited volunteers (33.0 % White, 32.5 % Mexican American, and 34.5 % African American). MAIN MEASURES: We evaluated the level of agreement with six previously described HIV conspiracy beliefs, trust in medical research, and willingness to participate in HIV vaccine research. Multivariate models were used to compare these parameters among the three racial/ethnic groups while controlling for the potential confounding effects of socioeconomic status, access to health care, and other demographic factors. RESULTS: African Americans, Mexican Americans, and whites had similar levels of distrust in medical research. African and Mexican Americans were more likely to endorse one or more of six HIV conspiracy beliefs than whites (59.0 % and 58.6 % versus 38.9 %, respectively, P < 0.001), but were significantly more willing to participate in HIV vaccine research (ORs 1.58, CI 1.10–2.25 and 2.53, CI 1.75–3.66, respectively). Among respondents of all racial/ethnic groups, endorsing HIV conspiracy beliefs was not associated with willingness to participate in research. CONCLUSIONS: HIV conspiracy beliefs, while common among all racial and ethnic groups in the United States, do not preclude willingness to participate in HIV prevention research.